Upaya Peningkatan Kualitas Kandungan Gizi Tempe Di Dusun Gentong Gundik Slahung Ponorogo - Trisna D. N. Rodhiyah; Ahmad Kirom (Institut Agama Islam Sunan Giri Ponorogo, 2025)
In Indonesia itself, tempeh is a traditional food made from soybeans and is very much liked by all people, both upper and lower middle class. Industrial processes in Indonesia are mostly done at home or home industry, one of which is the tempe craft home industry in Gundik Village, Kec. Slahung, Kab. Ponorogo. This research is to improve the quality of the nutritional content of tempeh for health based on an example in Gundik Village, Slahung which maintains the sterility of tempeh from the start of manufacture. This article is also devoted to fulfilling a research assignment within the framework of KPM (Public Service Lecture) Sharia students at the Sunan Giri Ponorogo Islamic Institute of Religion. This study uses Asset Based Community-driven Development (ABCD) method, is the technique of conducting appreciative interviews. The results of this study are to show the naturalness of the process of making tempeh and its cleanliness so that it maintains the nutritional content in tempeh.